Innovation Product and Halal Labelization in Buying Repurchase - Aditi, Bunga (Universitas Prasetiya Mulya, 2019)
Indonesia is a developing country which has many Small and Medium Firms (SMEs). It has a vital role in development and economic growth. The purpose of this research is to know and analyze the effect of product innovation and halal labelling in buying Repurchase. The method used in this study is descriptive analysis method by describing the data. It has been collected without intending to make conclusions to the public or generalization. Data analysis used is Multiple Linear by using SPSS software. The results showed that product innovation and halal labeling simultaneously had a positive and significant effect on buying repurchase. Partially Product Innovation and Halal Labelization have positive and significant effect in buying repurchase. Price as a moderating variable can strengthen the influence of product innovation and halal labelization in buying repurchase in SMEs of Langkat.Keywords: Innovation Product, Halal Labelization, Buying Repurchase, Price(1) Department of Management, Harapan University of Medan, Kota Medan, Indonesia* Corresponding Author https://doi.org/10.21632/irjbs.12.1.87-100